Association between LDL-C/HDL-C ratio and first stroke in hypertensive patients: a prospective cohort study - Yu, Chao; Wu, Meihui; Zhu, Lingjuan; Wang, Tao; Zhang, Weifang; Zhou, Wei; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2025)
BackgroundExisting evidences regarding the association between the ratio of low-density lipoprotein cholesterol (LDL-C) to high-density lipoprotein cholesterol (HDL-C) and first stroke in hypertensive patients remains limited. This study aims to assess the role of LDL-C/HDL-C ratio in the risk of first stroke in Chinese hypertensive patients.Methods and resultsThis prospective cohort study encompassed 12, 893 hypertensive patients from the Chinese Hypertension Registry. Cox proportional hazards regression, restricted cubic spline (RCS), and subgroup analysis were applied to evaluate the association between LDL-C/HDL-C ratio and first stroke. The hazard ratio (HR) and 95% confidence interval (CI) were used to estimate the strength of the association. The mean age of all participants was 63.7 ± 9.5 years, and 531 cases of first stroke occurred, with an average follow-up time of 3.9 years. In the fully adjusted model, each 1-unit increase of LDL-C/HDL-C ratio raised the risk of first stroke by 43% (HR=1.43, 95% CI: 1.22–1.67). Compared with patients in the Q1 of LDL-C/HDL-C ratio, the adjusted HRs of stroke for those in Q2, Q3, and Q4 were respectively 1.32 (95% CI: 1.03,1.70), 1.49 (95% CI: 1.14, 1.96), and 1.94 (95% CI: 1.45, 2.59), with a statistically significant trend (P for trend < 0.001). Analyses using restricted cubic spline confirmed the linear association between the LDL-C/HDL-C ratio and first stroke. Subgroup analysis revealed a stronger association between the LDL-C/HDL-C ratio and first stroke in drinkers (P for interaction=0.024).ConclusionA high LDL-C/HDL-C ratio may increase the risk of first stroke in hypertensive patients, especially among current drinkers.